Sunlight assisted improved photocatalytic degradation of rhodamine B using Pd-loaded g-C3N4/WO(3)nanocomposite - Alman, Vidya; Singh, Kirti; Bhat, Tejasvinee; Sheikh, Arif; Gokhale, Suresh (Applied Physics A-Materials Science & Processing, 2020)
Effective photocatalytic degradation of organic toxic dyes from industrial effluents using low-cost nanomaterials as a photocatalyst under sunlight promises for water purification and environmental recovery. The present work is focused on the synthesis of Palladium (Pd) loaded g-C3N4/WO(3)nanocomposite using a facile method and its photocatalytic degradation of Rhodamine B (RhB) using under sunlight. The results of the photocatalytic dye degradation experiment show that Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst degrades 98% of RhB in 40 min of sunlight illumination. This remarkable photocatalytic degradation performance of Pd loaded g-C3N4/WO(3)nanocomposite mainly attributed due to their intrinsic photocatalytic activity and co-existence of enhanced light absorbance and efficient charge transfer process in between the g-C3N4/WO(3)heterojunction. The durability testing experiments indicate that Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst could be effectively reused and possesses high photochemical structural stability even after several recycle process. Present experimental results demonstrated highly encouraging photo-degradation response of Pd loaded g-C3N4/WO(3)nanocomposite photocatalyst at outdoor conditions paves the way for the development of energy conversion and environmental remediation process.
Keywords: Nanocomposite; Palladium loading; Photocatalysis; Photodegradation; Rhodamine B; Sunlight